IDENTIFIKASI MISKONSEPSI DALAM MENYELESAIKAN SOAL PERTIDAKSAMAAN LINEAR SATU VARIABEL YANG MEMUAT NILAI MUTLAK - Yulya Kusumawati; Halini Halini; Hamdani Hamdani (UNIVERSITAS TANJUNGPURA, 2021)
Abstract This research aims to describe the forms of student misconceptions and the factors that cause misconceptions experienced by students in solving linear inequality problems with one variable containing absolute values in class X SMA Muhammadiyah 1 Pontianak. The subjects of this research were students of class X IPA 3 SMA Muhammadiyah 1 Pontianak, totaling 25 students. The research uses descriptive method as the research method. Case study is a form of research used. The results of the research revealed that the research subjects experienced five forms of misconception, namely notation misconceptions experienced by 1 student or by 4%, generalizing misconceptions experienced by 3 students or by 12%, misconceptions of the application of rules experienced by 6 students or by 24%, calculation misconceptions experienced by 2 students or by 8%, and specialization misconceptions experienced by 3 students or 12%. The misconceptions experienced by these students are caused by wrong intuition and incomplete reasoning, where students' intuitive thoughts that arise spontaneously when solving problems are still wrong and students' reasoning or logic is still wrong in drawing conclusions and being too broad in generalizing. Keywords: Misconceptions, Two-Tier Diagnostic Test, One Variable Linear Inequality Problem with Absolute Values